Microvesicles from cerebrospinal fluid of patients with Alzheimer’s disease display reduced concentrations of tau and APP protein - Spitzer, Philipp; Mulzer, Linda-Marie; Oberstein, Timo; Munoz, Luis Enrique; Lewczuk, Piotr; Kornhuber, Johannes; Herrmann, Martin; Maler, Juan Manuel (Scientific Reports, 2019)
Microvesicles are small membranous particles generated during cellular activation or stress. The analysis of the content and the surface of microvesicles allow conclusions about the cells they are originating from and the underlying pathology. Therefore, CSF microvesicles have been suggested to be promising targets to monitor the (etio)pathology of neurodegenerative diseases. Microvesicles in the CSF of 15 patients with Alzheimer’s disease and 15 controls were analyzed by flow cytometry regarding the levels of CD3, CD4, CD45, CD64, BACE1, Aβ, APP and tau. The results were replicated in a second cohort comprising 14 patients with Alzheimer’s disease and 9 controls. The levels of tau and APP were reduced in microvesicles of Alzheimer’s disease patients. A significant change was neither observed in the number of microvesicles nor in the expression of the other antigens. Tau and APP in microvesicles separated patients with Alzheimer’s disease from controls with an AUC of 0.84 and 0.89 respectively. We conclude that tau and APP in CSF microvesicles are promising biomarkers which could directly provide information about the Alzheimer pathology on a cellular level.
CRIS-Team Scopus Importer:2019-05-21